Meiotic dynamics in a unique Australian marsupial provide new insights into the evolution of neo-sex chromosomes in the early stages of differentiation - Laia Marín-Gual; Laia Marín-Gual; Carolyn J. Hogg; J. King Chang; Andrew J. Pask; Marilyn B. Renfree; Paul D. Waters; Aurora Ruiz-Herrera; Aurora Ruiz-Herrera (Frontiers in Cell and Developmental Biology)
Understanding the origin and fate of sex chromosomes has been one of the most intriguing questions in biology. In therian (marsupial and eutherian) mammals, most species are characterized by a heteromorphic XX female XY male sex chromosome system. It is commonly accepted that they originated from a pair of autosomes after gaining a sex-determining function, leading to recombination suppression and subsequent Y chromosome degeneration. Unlike eutherian sex chromosomes which share a pseudo-autosomal region (PAR), the marsupial sex chromosomes are typically tiny and lack any homology. However, there is a lack of empirical evidence on biological systems that represent early stages of sex chromosome differentiation. Here, we describe the meiotic dynamics of an XY1Y2 system in the greater bilby (Macrotis lagotis: family Thylacomyidae) that resulted from a fusion between an autosome and the ancestral X chromosome. We compared the similarities and differences in the regulation of meiosis in two other Australian marsupial species with different sex chromosome systems: the tammar wallaby (Macropus eugenii: family Macropodidae) and the fat-tailed dunnart (Sminthopsis crassicaudata: family Dasyuridae), both with the ancestral XY system. We performed a cytological analysis of meiotic prophase I, including the study of chromosome synapsis, double strand break formation (as a proxy of recombination) and meiotic sex chromosome inactivation. Our results suggest that the neo-PAR in the greater bilby represents an early stage of differentiation, providing new insights into sex chromosome evolution.